Relationship between characteristics of water polo players and efficacy indices - Alcaraz, P. E.; Abraldes, J. A.; Ferragut, C.; Vila, H.; Rodriguez, N.; Argudo, F. M. (The Journal of Strength and Conditioning Research, 2012)
The aim of this study was to define and examine the relationships between the anthropometrical characteristics, maximum isometric grip strength, and competition throwing velocities and efficacy indices in high-level water polo player. Eleven elite trained male water polo players participated in this study. During preseason training, the following measures were taken: standard anthropometry (height, body mass, arm spam, skinfolds, body girths, and skeletal breadths) and grip strength. During official European Competitions (n = 7), efficacy indices (offensives: shot definition, resolution, precision, blocked and defensives: shot resolution when defending and shots stopped when defending), average and maximum throwing velocities from all the participants by zones and in some offensive tactical phases (even, counterattacks and power play) were also determined. Throwing velocities were different (p = 0.05) between some of the offensive tactical phases (even = 17.9 ± 2.4 vs. power play = 16.7 ± 2.6 m/s). In addition, significant correlations were found between competitive throwing velocities and different offensive efficacy indices. We concluded that there were significant correlations between conditioning and performance variables with anthropometrical characteristics and offensive tactical indices (blocked shots received and shot precision). Coaches should pay attention to these indices for the development of performance throughout the season